AB0905 Relationship between Lower Socioeconomic Level and Outcome Measures in Juvenile Systemic Lupus Erythematosus. (10th June 2014) - Katsicas, M.M.; Russo, R.
Abstract : Background: Juvenile Systemic Lupus Erythematosus (JSLE) is known to occur in all populations across the globe. In many respects SLE is similar across regions in its spectrum of clinical features, but the severity of the disease and comorbidity are appreciably different in the developing countries. Different epidemiologic studies showed that lower socioeconomic level is consistently associated with poor outcome in SLE. Objectives: To assess the relationship between socioeconomic variables and outcome measures in JSLE. Methods: Consecutive patients with JSLE according to the ACR criteria were included. They were seen at the pediatric rheumatology clinic of a tertiary hospital during the last 15 years. Onset of the disease of all of them were nearly the first visit to our center. Familial socioeconomic level was evaluated by Graffar scale, which includes the following areas: profession of the household head, level of education, main source of income, housing characteristics. Each variable is assigned a punctuation and points are summed. Scoring may range between 4 and 20 points. Lowter socioeconomic level was defined as Graffar score ≥13 points. Patients were divided into 2 groups according to their Graffar scoring (<13 and ≥13). Assessed variables were: age at disease onse, gender, ethnicity, distance in Km to a specialized center. Outcomes included: a) activity (percentage of time with active disease (SLEDAI>4), percentage of time with low complement (C3 <95 mg/dl and C4 <18 mg/dl), percentage of time with positive anti DNA, presence of flare according to Lupus Foundation of America; b) organ damage using SLICC; c)proliferative/severe nephritis and d)deaths. The following variables were also evaluated: admissions, missing visits, incomplete treatment. Observation time compromised the last year of follow up. Differences between groups were analized by Wilcoxon Rank Sum Test and association test models. Results: Forty-eight patients were included (42 F, 6 M). Age at onset (median): 12.6 years. Follow up: 5.5 (1.1-14.7) years. Overall outcome measures showed: percentage of time with active disease: 20%, percentage of time with low C3 37%, with low C4 100%; percentage of time with positive anti DNA 25%; incidence of flares 0.3/year. b) SLICC >0: 57%; c)proliferative/severe nephritis: 46% and d) deaths: 2%. Other variables: admissions 0.20/year, missing visits:25%, incomplete treatment:15%. Lower socioeconomic level was observed in 27 patients (56%). No differences were found among groups in gender, ethnicity, distance in km to specialized center. Outcomes in both groups showed a significant association between lower socioeconomic level and incidence of flares (p=0, 014) and prevalence of proliferative/severe nephritis (p=0.05). Lower SE group was significantly associated with admissions (p=0, 02), missing visits (p=0.03) and incomplete treatment (p=0.01). Graffar's areas analysis showed: flares/income (p=0.00001), nephritis/income (p=0.05) Admission also was associated with income (p=0.01). Lower level of education was associated with missing visits (p=0.05). Conclusions: Significant association between lower socioeconomic level and incidence of flares and proliferative/severe nephritis was found. Lower income and lower level of education could be considered as predisposing factors for a worse quality of care in patients with JSLE Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5486